Functional, ergonomic, and usability testing of the dental hypnosis monitoring device: Study experimental - Muttaqin, Akmal; Yubiliana, Gilang; Suryani, Mira (Fakultas Kedokteran Gigi Universitas Padjadjaran, 2025)
ABSTRACTIntroduction: The Dental Hypnosis Monitoring Device (DHMD) is a tool designed to monitor patients' consciousness levels during dental hypnosis, with the aim of reducing anxiety during dental procedures. This study was conducted to evaluate the functionality, ergonomics, and usability of the DHMD through a series of structured tests. This study aims to evaluate the functionality, ergonomics, and usability of the DHMD in relation to patient anxiety during dental treatment procedures. Methods: The research employed a quantitative approach, with functional testing based on Black Box Testing, ergonomic evaluation utilized a Likert-scale questionnaire, and usability testing was performed using the User Experience Questionnaire (UEQ). The study took place at the LADOKGI R.E. Martadinata Dental and Oral Hospital from January to February 2024, involving 11 patients aged 20–58 years as respondents. Results: The Dental Hypnosis Monitoring Device successfully performed its primary functions, including the display of brainwaves, visual output, and audio features, meeting the expectations of all respondents. The ergonomic assessment yielded a feasibility percentage of 84.85%, classified as highly feasible, though some improvements in physical design are still required. The usability test produced excellent scores across most scales, such as attractiveness, efficiency, and clarity, with a comparatively lower score in novelty. Conclusion: The Dental Hypnosis Monitoring Device has demonstrated functionality, ergonomic suitability, and effectiveness in helping to manage patient anxiety during dental treatments. This study recommends further advancements in design and technology to enhance the user experience.KEYWORDS: Dental hypnosis monitoring device (DHMD), dental hypnosis patient anxiety, functional testing, ergonomic testing, usability testingUji Fungsional, ergonomis, dan usabilitas dental hypnosis monitoring device dalam mengelola kecemasan pasien selama prosedur perawatan gigi: Studi experimentalABSTRAK Pendahuluan: Dental Hypnosis Monitoring Device (DHMD) merupakan alat yang dirancang untuk memantau tingkat kesadaran pasien selama hipnosis gigi, bertujuan mengurangi kecemasan pasien pada prosedur perawatan gigi. Penelitian ini bertujuan untuk mengevaluasi fungsionalitas, ergonomis, dan usabilitas DHMD dalam kecemasan pasien selama prosedur perawatan gigi Metode: penelitian ini menggunakan pendekatan kuantitatif dengan uji fungsional berbasis Black Box Testing, uji ergonomi melalui kuesioner skala Likert, dan uji usabilitas menggunakan user Experience Questionnaire (UEQ). Penelitian dilakukan di Rumah Sakit Gigi dan Mulut LADOKGI R.E Martadinata pada Januari-Februari 2024, dengan melibatkan 11 pasien berusia 20-58 tahun sebagai responden. Hasil: Dental Hypnosis Monitoring Device berhasil menampilkan fungsi utama, seperti gelombang otak, visual, dan audio, sesuai harapan ketika digunakan oleh semua responden. Tingkat ergonomi mendapat persentase kelayakan 84,85%, tergolong sangat layak, meskipun masih ada potensi peningkatan pada aspek desain fisik. Sementara itu, uji usabilitas menunjukkan skor ”excellent” pada hampir semua skala, seperti daya tarik, efisiensi, dan kejelasan, dengan skor kebaruan relatif lebih rendah. Simpulan: Dental Hypnosis Monitoring Device terbukti dari aspek fungsional, ergonomis, dan kegunaan dapat membantu pengelolaan kecemasan pasien selama perawatan gigi. Penelitian ini merekomendasikan pengembangan lebih lanjut pada aspek inovasi desain dan teknologi untuk meningkatkan pengalaman pengguna. KATA KUNCI: Dental hypnosis monitoring device (DHMD), hipnosis gigi, kecemasan pasien, uji fungsional, uji ergonomis, uji usabilitas